The Teaching Reading Comprehension Through Small Group Discussion at The Eighth Grade Students of SMP Negeri 3 Parepare - Megawati (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2019)
Based on the result of research observation, the researcher found that the student’s reading ability is still low. It was caused by the effect of less strategy in teaching, for this reason the students confuse how to get specific information from the reading text easily. For this reason, Small Group Discussion starategy.In this case, Small Group Discussion is a strategy that able to guide the students in recording the information related to the elements of the text.Then, the objective of this research is to find out whether or not the use of Small Group Discussion able to improve the student’s reading comprehension of the eighth grade students of SMP Negeri 3 Parepar. The researcher applied quasi-experimental, with two ground pre-test and post-test. The samples were taken by cluster random sampling that consisted of 60 students that taken from two classes of the population at the eighth grade students of SMP Negeri 3 Parepare. One class as an experimental class and the other one as an control class. The result of the research the use of Small Group Discussion improved the students reading comprehension of SMP Negeri 3 Parepare. It is proved by the result of the statistical analysis by using manual calculation where the significant value of pre test ( 1.14 ) was lower than the level of significant ( 2.000 ).and post test ( 4.70 ) was higher that the level significant ( 2.000). Those indicated that HI was accepted and HO was rejected. It means that Small Group Discussion cam Improve the reading comprehension of the eighth grade students of SMP Negeri 3 Parepare.